1989
DOI: 10.1159/000153876
|View full text |Cite
|
Sign up to set email alerts
|

In situ Genetic Complementation Analysis of Cells with Generalized Peroxisomal Dysfunction

Abstract: Most patients with Zellweger syndrome, neonatal adrenoleukodystrophy, infantile Refsum disease and hyperpipecolic acidemia are characterized by a deficiency of peroxisomes. We have developed a simple cytological method for the in situ detection of genetic complementation among and between these patients who are clinically and biochemically defined as having generalized peroxisomal dysfunction. This technique should facilitate both complementation studies in these disorders and investigations into the biogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Although [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]pristanic acid is not available commercially, it is readily synthesized (33) and the product can be stored indefinitely. In addition, there are a number of advantages in using this substrate for the diagnosis of peroxisomal disorders (see below) which easily justify its synthesis and use.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]pristanic acid is not available commercially, it is readily synthesized (33) and the product can be stored indefinitely. In addition, there are a number of advantages in using this substrate for the diagnosis of peroxisomal disorders (see below) which easily justify its synthesis and use.…”
Section: Discussionmentioning
confidence: 99%
“…Using the distribution of catalase immunofluorescence as an indicator of whether complementation had occurred between two cell lines (8), cell line 1 was placed in their complementation group A, cell line 3 in their group C, and cell lines 6,7,8,9, and 10 in their group E (Shimozawa, N., personal communication). Cell lines 11 and 12 belonged to a newly identified complementation group (3).…”
Section: Patient Cell Lines and Tissue Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the overlapping clinical features in these patients and the similar bio chemical abnormalities, the relationship be-tween these diseases has been investigated by genetic complementation analysis following somatic cell fusion. Using this approach, we and others [2][3][4][5] have shown genetic hetero geneity among Zellweger syndrome patients and have also shown that some patients clin ically identified with other peroxisomal dis eases (i.e. NALD.…”
Section: Introductionmentioning
confidence: 97%